Situs Pulau Ujir di Kepulauan Aru: Kampung Kuno, Islamisasi dan Perdagangan - Wuri Handoko (Kapata Arkeologi, 2016)
Ujir ancient village on the island, is the site of settlement that shows the development of the Islamic period and colonial settlements in the territory of Aru Islands. Various archaeological data has been discovered, indicates the site serves as a growing settlements with the activities of the Muslim settlers and until recently has shown progress as one of the Muslim villages were quite advanced in the Aru Islands. This study is to explore the traces of Islamization and commercial developments in the Aru Islands, with the main focus in the Ujir Island to analyze the are role in the development of Islamization and commerce in the Aru Islands in the past. Study focused on the archaeological data collected from survey and excavation. The results showed that the old village site Ujir Island, called Site Uifana, is the site of settlements in the past is likely to be one of the centers spread of Islam in the Aru Islands which was later destroyed and abandoned during the influence of the entry of European colonization and later the Japanese. Ujir Island may also be a bridge in trade flows involving the surrounding area in the path of the spice trade and exotic commodities of Aru Islands.Kampung kuno di Pulau Ujir, merupakan situs permukiman yang menunjukkan perkembangan permukiman masa Islam dan kolonial di wilayah Kepulauan Aru. Penelitian ini menemukan, berbagai data arkeologi yang menunjukkan bahwa Pulau Ujir merupakan situs pemukiman yang maju dan berperan dalam jaringan Islamisasi dan perdagangan di kawasan Kepulauan Aru. Hasil penelitian memperliatkan bahwa situs kampung tua Pulau Ujir, yang disebut Situs Uifana, adalah situs permukiman yang pada masa lampau menjadi salah satu pusat penyebaran Islam yang kemudian hancur dan ditinggalkan pada masa pengaruh kolonialisasi Eropa  dan  Jepang. Pulau Ujir juga menjadi jaringan perdagangan yang melibatkan kawasan sekitarnya dalam jalur perdagangan rempah dan komoditi eksotik, seperti burung cendrwaasih dan mutiara di  Kepulauan Aru.